Security management for occupational safety - Land, Michael (Industrial engineer) (CRC Press, 2014)
"This book is written for the occupational safety managers who want to be more effective managers as well as for the students who would like to become occupational safety managers as their profession. A critical thinking approach provides a methodical process to look at the occupational safety management functions so they can better tailor safety to any organization. This book presents the most accurately balanced picture of occupational safety management functions by using a critical thinking approach to interpret data as a tool for providing more effective safety management"-- Provided by publisher.
Keywords: Industrial safety -- Management.; elektronické knihy; electronic books